What Works in Israeli Prison-Based Sex Offender Rehabilitation Programs: Program Participants’ Perspective - Geiger, Brenda (International journal of offender therapy and comparative criminology, 2018)
This study invited 10 of the 22 sex offenders enrolled in a prison-based rehabilitation program in one of the prisons in Israel to engage in the two first of the 4-D (Discover, Dream, Design, and Deliver) stages of the Appreciative Inquiry . Consistent with the responsivity principle, and the IA tenets, program participants were interviewed to Discover components to which they were responsive and Dream/envision additional ones that would increase engagement and progress. Content analysis of the interviews indicated that despite the initial decision to enrol based on external incentives, participants eventually engaged in group therapy and expressed the desire to understand and regulate their sexual behaviour. While the the modules of Cognitive Behabioral Group Therapy (CBT) were viewed as assets, the lack of sufficient recruitment criteria, the large therapy group size, and its open-ended structure were mentioned as impediments reaching therapeutic goals. Social workers/therapists were criticized for their request that they be informers, and for their accusative therapeutic style whenever sexual issues were broached. Recommendations derived from the offenders’ narrative were to increase staff professionalism to create a therapeutic alliance that promotes trust and open communication. Criminal justice practitioners may then take up the challenge of the never-ending process of Appreciative Inquiry to Design and Deliver program components envisioned by the participants to increase participants’ responsivity to the program and thus its effectiveness.